Chromosomal studies on two endangered catfishes-Ompok bimaculatus (Bloch) and Ompok pabda (Hamilton-Buchanan) - SHARMA, RUPAM (The Indian Journal of Animal Sciences, 2011)
Chromosomal studies are the basic requisite for genetic improvement program and for co servation of wild gene pool. The catfishes Ompok bimaculatus and Ompok pabda are being endangered due to the habItat destructIo and lack of proper management of the stock. For the present karyotypic study on these 2 freshwate:- endangered catfishes, 25 samples of each species were examined and 307 and 330 chromosome spreads of O. blmacul tus and O. pabda, respectively, were screened. The study revealed the presence of dip oid chromoson:e umber as 42 wl h the chromosome formula of 12 metacentric, 14 submetacentric and 16 subtelocentnc and telocentnc In both the specIes. The karyotype is characterized by the fundamental arm number (NF) of 68. Â